Sosialisasi Pencatatan Perkawinan di Desa Wanawali Kecamatan Cibatu Kabupaten Purwakarta - Siti Nurul Latifah; Yuwan Fijar Anugrah; Tajul Muttaqien (STIKes Ibnu Sina Ajibarang, 2024)
The aim of carrying out this outreach activity is to increase the legal knowledge and awareness of the Wanawali village community regarding the urgency of registering marriages to obtain a marriage certificate. This activity was carried out because there are a set of problems currently being faced, especially regarding the lack of public awareness regarding registering marriages. This condition is a systemic impact of the general public's low level of understanding in Wanawali Village, Cibatu District, Purwakarta Regency regarding the regulations governing marriage and their lack of awareness regarding the importance of registering marriages in order to obtain a marriage certificate. The method used in this activity is Participatory Action Research (PAR). As an effort to obtain a marriage certificate at the Religious Affairs Office (KUA), the applicant submits a marriage isbat application to the Religious Court by attaching several requirements. The requirements that must be met for submitting a marriage Itsbat application are listed in the Compilation of Islamic Law Article 7 paragraphs (1), (2), (3) and (4). The determination of Itsbat Nikah will be granted by the religious court judge if these conditions are met. By granting the application for a Marriage Certificate, a marriage that has been solemnized according to religious law can be requested to be registered with the Marriage Registrar (VAT) Officer at the sub-district KUA covering the area, bringing a copy of the decision to issue a Marriage Certificate Excerpt. and The results of the activity show that after being given socialization, the participants have clear and complete knowledge regarding: (1) knowledge about Civil Law, especially Marriage Law which is related to procedures for registering marriages, (2) knowledge about the impact and consequences of having a marriage registration.